Determinants of Knowledge and Behaviours of Indonesian Health Care Providers toward the Prevention of COVID-19 - Yoyok Bekti Prasetyo; Alhisna Fitri Setyamardina; Henik Tri Rahayu; Titih Huriah (Universitas Padjadjaran, 2021)
Background: Due to the high risk of exposure of Health Care Providers (HCPs) at the forefront of the COVID-19 responses, HCPs’ knowledge and prevention behaviors towards COVID-19 have become crucial parts of their job performances. Purpose: This study aims to identify the level of knowledge and prevention behaviors of HCPs toward COVID-19 and factors associates. Methods: This study utilized a cross-sectional research design. The samples consisted of 182 HCPs in Malang, East Java Province, Indonesia. The data were collected through structured self-developed online questionnaires, consisting of socio-demographic characteristics, knowledge, and prevention behaviors. The data were treated as categorical data types and then analyzed using frequency distribution, chi-squares, and logistic regression performed by SPSS 22 software. Results: The HCPs working at hospitals have about one time better knowledge than those who work at public health centers, clinics, and pharmacies (COR = 1.03; 95% CI: 0.72-14.76). Nurses have 3.4 times better knowledge than other HCPs (COR = 3.43; 95% CI: 0.27-43.84). HCPs with 5 to 10-year experience have 6.4 times better prevention behavior than those with less than five years or over 10-year experience (COR = 6.42; 95% CI: 0.57-72.76). Conclusion: The knowledge and prevention behaviors of HCPs toward COVID-19 prevention were influenced by age, residence area, occupation, and the length of working experience. Therefore, HCPs need to understand the new healthy habits and actively contribute to COVID-19 intervention programs.